Sexual Dimorphism of Immune Responses: A New Perspective in Cancer Immunotherapy - Capone, Imerio; Marchetti, Paolo; Ascierto, Paolo Antonio; Malorni, Walter; Gabriele, Lucia (Frontiers in Immunology, 2018)
Nowadays, several types of tumors can benefit from the new frontier of immunotherapy, due to the recent increasing knowledge of the role of the immune system in cancer control. Among the new therapeutic strategies there is the immune checkpoint blockade (ICB), able to restore an efficacious antitumor immunity and significantly prolong the overall survival (OS) of patients with advanced tumors such as melanoma and non-small cell lung cancer (NSCLC). Despite the impressive efficacy of these agents in some patients, treatment failure and resistance are frequently observed. In this regard, the signaling governed by IFN type I (IFN-I) has emerged as pivotal in orchestrating host defence. This pathway displays different activation between sexes, thus potentially contributing to sexual dimorphic differences in the immune responses to immunotherapy. This perspective article aims to critically consider the immune signals, with particulat attention to IFN-I, that may differently affect female and male antitumor responses upon immunotherapy.